2001
DOI: 10.1111/0022-4537.00200
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Sexism: Evidence for Its Incidence, Nature, and Psychological Impact From Three Daily Diary Studies

Abstract: Three daily diary studies were conducted to examine the incidence, nature, and impact of everyday sexism as reported by college women and men. Women experienced about one to two impactful sexist incidents per week, consisting of traditional gender role stereotypes and prejudice, demeaning and degrading comments and behaviors, and sexual objectification. These incidents affected women's psychological well-being by decreasing their comfort, increasing their feelings of anger and depression, and decreasing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
649
3
14

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(698 citation statements)
references
References 27 publications
(31 reference statements)
32
649
3
14
Order By: Relevance
“…Furthermore, most studies examining objectification perpetration have focused on very attractive women (e.g., swimsuit models; Bernard et al 2012;Loughnan et al 2010;Vaes et al 2011;celebrities;Heflick and Goldenberg 2009). As a result, less is known about when and why people objectify women who are less attractive, even though average and less attractive women self-report objectification (Kozee et al 2007;Swim et al 2001). Additionally, we sought to extend previous research revealing that objectification causes dehumanization by examining whether women who appear less warm or less competent are objectified more than women who appear more warm or more competent.…”
Section: Overview and Hypothesesmentioning
confidence: 99%
“…Furthermore, most studies examining objectification perpetration have focused on very attractive women (e.g., swimsuit models; Bernard et al 2012;Loughnan et al 2010;Vaes et al 2011;celebrities;Heflick and Goldenberg 2009). As a result, less is known about when and why people objectify women who are less attractive, even though average and less attractive women self-report objectification (Kozee et al 2007;Swim et al 2001). Additionally, we sought to extend previous research revealing that objectification causes dehumanization by examining whether women who appear less warm or less competent are objectified more than women who appear more warm or more competent.…”
Section: Overview and Hypothesesmentioning
confidence: 99%
“…Future studies may also want to include a daily diary method of assessing experiences of racial discrimination in order to reduce the errors associated with retrospective reports. For example, Swim, Hyers, Cohen, and Ferguson (2001) used a daily diary method to study women's experiences of gender discrimination. Moreover, the current results showed that students who had lived in the United States for a longer period of time reported higher levels of perceived discrimination.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…and their negative sequelae (i.e., emotional distress), based on conceptualizations of stigma as a stressor (see Miller & Kaiser, 2001). The link between emotional distress and stigmatizing events, as well as support for the hypothesis that discriminating events cause distress, has been documented in empirical studies on gender and race/ethnicity based stigma (Landrine, Klonoff, Gibbs, Manning, Lund, 1995;Landrine & Klonoff, 1996;Swim, 2001). Several empirical studies among PLH have documented the association between HIV-stigma and depression (Lee, Kochman, Sikkema, 2002;Lichtenstein, Laska, & Claire, 2002;Crandall & Coleman, 2002;Laryea & Gien, 1993;Berger, Ferrans, & Lashley, 2001), as well as anxiety, alienation, social conflict, and poor social support (Berger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%